IMPROVING SHORT WRITING ABILITY USING AUDIO VISUAL MEDIA IN ACCOUNTING STUDENTS OF SMK NEGERI 1 CITY OF SERANG - juwartini juwartini (Jurnal Ilmu Pendidikan Ahlussunnah, 2022)
This study aims to determine: (a) does the use of audio-visual media affect the ability to write short stories for class XI students of SMK Negeri 1 Serang City? (b) how high is the increase in the ability to write short stories for class XI students of SMK Negeri 1 Serang City after using audio-visual media?. This research uses classroom action research with three cycles. Each cycle consists of four stages, namely: design, activities and observations, reflection, and revision. The target of this research is 35 students of Class XI Accounting 1 SMK Negeri 1 Serang City in the 2018/2019 academic year. Data collection techniques using student work, observation sheets of teaching and learning activities. From the results of the analysis obtained information that student achievement has increased from cycle I to cycle III. In the first cycle, students who got a score of 10-60 were 16 students (45.71%), a score of 61-70 were 11 students (31.43%), a score of 71-85 was 8 students (22.86%), and the value of 86-100 there are 0 students. In the second cycle, there were 0 students who got a score of 10-60, a score of 61-70 had 24 students (68.57%), a score of 71-85 had 11 students (31.43%), and a score of 86-100 contained 0 student. In the second cycle, there were 0 students who got a score of 10-60, a score of 61-70 had 3 students (8.58%), a score of 71-85 had 32 students (91.42%), and a score of 86-100 contained 0 student. The conclusion of this research is that the use of audio-visual media can improve the ability to write short stories for students of class XI Accounting 1 SMK Negeri 1 Serang City. Audio-visual learning media can be used as an alternative Indonesian language learning media.